The European Charter for Sustainable Tourism (ECST) as a Tool for Development in Rural Areas: The Case of Vesuvius National Park (Italy) - Monaco, Salvatore; Freire Varela, Antón; Guarino, Guido; Corbisiero, Fabio (Agriculture (Basel), 2025)
The study investigates how agriculture can serve as a driver of sustainable tourism and local development within the Vesuvius National Park under the European Charter for Sustainable Tourism (ECST) framework. Based on 14 semi-structured interviews with farmers, tourism operators, cultural institutions, and producer consortia, the findings reveal that agriculture plays a central role not only as a productive sector but also as a custodian of biodiversity, identity, and territorial resilience. Stakeholders emphasised the economic and symbolic value of traditional crops, highlighting how farm-based experiences, product certifications, and civil-society networks strengthen community cohesion and diversify visitor flows. Nevertheless, tourism remains predominantly concentrated in the vicinity of the volcano’s crater, thereby excluding the park’s other trails, limiting the positive impacts on rural and peripheral areas. Practical implications point to the need for improved mobility infrastructure, cross-sector coordination, and targeted incentives to link agrotourism circuits with regional branding and EU sustainability policies. Overall, the study shows that integrating agriculture into tourism governance can foster more inclusive, resilient, and territorially embedded forms of rural development in protected areas.